Prevalence and factors associated with diarrheal diseases among children below five years in selected slum settlements in Entebbe municipality, Wakiso district, Uganda - Robinah Nantege; Dickson Kajoba; Christopher Ddamulira; Fred Ndoboli; David Ndungutse (BMC, 2022)
Abstract Background Despite global interventions to prevent and control diarrhea, it still remains a public health problem leading to childhood morbidity and mortality majorly in developing countries. In Uganda, diarrhea is amongst the five leading causes of under-five mortality, contributing to more than 140,000 deaths every year and this accounts for 7.1% of all under-five mortalities in Uganda. Efforts to prevent and lower diarrheal diseases need to be informed by data on determinants of diarrhea. The study assessed factors associated with diarrheal diseases among children below five years in selected slum settlements in Entebbe municipality, Wakiso District, Uganda. Methods The study employed a cross-sectional study design covering 384 randomly selected households having children < 5 years old in the study area using quantitative research methods. Data was collected using close-ended questionnaires and diarrhea disease history was captured for the last month before the survey. Bivariate and multivariate logistic regression analyses were used to identify the risk factors associated with childhood diarrhea considering a 95% confidence level. Results The prevalence of Diarrhea disease in children among the selected slum settlements in Entebbe municipality was found to be at 62.4%. Access to water from a protected water source (deep well and borehole), presence of a vent in toilets, age, and child birth weight were found to be significantly associated with diarrheal diseases among children below five years in the selected slum settlements in Entebbe municipality. Conclusion The prevalence of childhood diarrhea among children < 5 years of age in selected slums of Entebbe municipality was found high. Use of water from a protected source, presence of a vent in toilets, age, child birth and weight were identified as predictors of diarrhea occurrence. These findings imply that community health education is urgently needed for fighting childhood diarrhea in the study area to eliminate the predisposing factors to diarrhea.